Whole Genome Sequencing Assessing Impact of Diabetes Mellitus on Tuberculosis Mutations and Type of Recurrence in India . (4th January 2022) - Mave, Vidya; Chen, Liang; Ranganathan, Uma Devi; Kadam, Dileep; Vishwanathan, Vijay; Lokhande, Rahul; S, Siva Kumar; Kagal, Anju; Pradhan, Neeta N; Shivakumar, Shri Vijay Bala Yogendra; Paradkar, Mandar S; Deshmukh, Sona; et al.
Abstract: Background: Evidence describing the impact of diabetes mellitus (DM) on the recurrence and mutation rate of Mycobacterium tuberculosis ( Mtb ) is limited. Methods: This study was nested in 3 cohort studies of tuberculosis (TB) patients with and without DM in India. Paired Mtb isolates recovered at baseline and treatment failure/recurrence underwent whole genome sequencing. We compared acquisition of single-nucleotide polymorphisms (SNPs), TB drug resistance mutations, and type of recurrence (endogenous reactivation [<8 SNPs] or exogenous reinfection [≥8 SNPs]) by DM status. Results: Of 1633 enrolled in the 3 parent cohorts, 236 (14.5%) had microbiologically confirmed TB treatment failure/recurrence; 76 Mtb isolate pairs were available for sequencing (22 in TB-DM and 54 in TB-only). The SNP acquisition rate was overall was 0.43 (95% confidence interval [CI], .25–.64) per 1 person-year (PY); 0.77 (95% CI, .40–1.35) per 1 PY, and 0.44 (95% CI, .19–.86) per 1 PY at treatment failure and recurrence, respectively. Significant difference in SNP rates by DM status was seen at recurrence (0.21 [95% CI, .04–.61]) per 1 PY for TB-only vs 1.28 (95% CI, .41–2.98) per 1 PY for TB-DM; P  = .02). No significant difference in SNP rates by DM status was observed at treatment failure. Acquired TB drug resistance was seen in 4 of 18 (22%) in TB-DM vs 4 of 45 (9%) in TB-only ( P  = .21). Thirteen (17%) participants had exogenous reinfection; the reinfection rate at recurrence was 25% (3/12) for TB-DM vs 17% (4/24) in TB-only ( P  = .66). Conclusions: Considerable intrahost Mtb mutation rates were present at recurrence among patients with DM in India. One-fourth of patients with DM had exogenous reinfection at recurrence. Abstract : Nested in 3 tuberculosis (TB) cohorts with and without diabetes mellitus (DM) in India, whole genome sequencing revealed considerable intrahost Mycobacterium tuberculosis mutation rates among TB-DM patients at recurrence in India. Exogenous reinfection was identified in one-fourth of patients with DM.